023 For how long should we monitor ED palpitation patients in the outpatient setting?. Issue 12 (21st November 2019) - Reed, Matt; Grubb, Neil; Lang, Chris; O'Brien, Rachel; Simpson, Kirsty; Padarenga, Mia; Grant, Alison; Tuck, Sharon; Keating, Liza; Coffey, Frank; Jones, Lucy; Harris, Tim; et al.
Abstract : Background: The IPED study showed that use of a smartphone-based event recorder (AliveCor) in ED patients presenting with palpitation or pre-syncope, increased the number of patients in whom an ECG was captured during symptoms over five-fold to more than 55% at 90 days (Reed MJ et al . Lancet eClinical Medicine 2019; 8: 37–46). The pocket sized AliveCor (now Kardia) mobile (AliveCor, San Francisco, USA) is a monitoring device that requires the patient to trigger the ECG recording. With minimal training, two fingers from each hand are placed on the monitor (which can be connected to the back of a smartphone) for 30 s to take an ECG recording. This pre-planned analysis looked at the time to symptomatic rhythm detection in the intervention (AliveCorgroup)to determine the optimum AliveCor device monitoring period in the outpatient setting. Method and results: Pre-planned sub study analysis of a randomised controlled multi-centre trial. Participants ≥16 years old presenting to 10 UK hospital EDs with palpitation or pre-syncope whose underlying ECG rhythm during these episodes remained undiagnosed after ED assessment were enrolled. Time to symptomatic rhythm detection was recorded and analysed. Conclusions: 243 participants were recruited over an 18-month period. A symptomatic rhythm was detected at 90 days in 69 (n=124; 55.6%; 95% CI 46.9–64.4%) participants in the intervention (AliveCor) group. 92.8% of patients who recorded a symptomatic rhythm during the 90 day period recorded this rhythm during the first 28 days (figure 1 /table 1 ). Conclusion: ED palpitation patients discharged with a smartphone-based event recorder such as the AliveCor should be reviewed after 4 weeks to enable efficient device usage and timely treatment if required. Patients in whom a diagnosis has not been made can be re-reviewed at 90 days. (1541 characters/285 words)